Organizational structure and administrative management in the electricity supply service in Peru, 2019 (SCIÉNDO INGENIUM, 2024)
The purpose of the research is to establish the relationship between organizational structure and administrative management in the electric power supply service in Peru, 2019. The population and the sample consisted of 771 and 126 employees, respectively, of an electric power supply company in Peru. A correlational design was used. The method used is inductive, hypothetical-deductive, analysis-synthesis, and the technique used is the survey. The results found are: 8.7% of the collaborators state that their level of organizational structure is deficient, 88.9% is regular and 2.4% is good; as for administrative management, 5.6% of the collaborators state that their level of administrative management is bad, 88.1% is regular and 6.3% is good. A positive relationship of 0.793 (good) was established between organizational structure and administrative management. The conclusion is that the employees consider that it is vital today to comply with their work as well as to know their organizational structure well in order to avoid disorder, improvisation and command authority.
Keywords: Organizational structure; administrative management; service; supply chain; energy